THE EFFECTS OF PERSONALITY AND SOCIAL COMPETENCE OF TEACHER PERFORMANCE AND ACHIEVEMENT ISLAMIC RELIGIOUS EDUCATION: A STUDY OF CLASS XI SMA KORPRI KARAWANG - Isyanto, Puji; Tuhagana, Aji; Hertina, Dede (International Journal of Psychosocial Rehabilitation, 2020)
Efforts to improve the quality of student achievement is highly dependent on the competence of teachers who formed professionalism. Among the components of the competence, it is personal competence and social competence. In this study focused on a secondary school teacher, both of these competencies is an exogenous latent variable which proved a positive effect on endogenous latent variable teacher performance. From the data processing is also obtained, that a number of indicators ranked at the top in contributing to the exogenous variables studied. The order of ranking indicators in personal competence, leadership, work ethic, self-development and achievement orientation; rank order indicators in social competence is komunikastif, objective, non-discriminatory, and authority. The results of these studies should receive attention, consideration and further elaboration by the parties with respect to the process of establishing and improving the competence of teachers, both in the administration PLPG, PPG In the office, PPG Prajabatan, education and teacher training in LPTK.